Produção artística visual no Amazonas na década de 1980 : análise iconográfica das obras da Pinacoteca do Estado do Amazonas. - Monteiro, Milene Mírian Araújo (2017)
This research aimed to analyze the artistic production in Amazonas through an iconographic study from selected works of the Amazonas State Art Gallery collection with the clipping of the last century's 1980s decade, to build a cultural artistic memory of visual production in the Amazonas State. First, was developed a preliminary survey of works from the Art Gallery collection then performed a critical inventory of artists and their works and finally the iconographic study. This research is characterized by being a bibliographic and documentary, in which were used sources and textual as well as visual varied documentation. The record of works was done through photographs and only of the works listed in the State Art Gallery's permanent exhibition. Once the selection of images was done, it went to the method of analysis which was iconographic, for a comprehension of the tendencies and stylistic aesthetic of this production, basing ourselves in Panofsky's art theory (1991), Warburg (2012) and for formal analysis Wölfflin (2015) and on visual arts in Amazonas, Páscoa (2011). The results of this research were recorded in a Android platform application and will be available in schools and even in the Amazonas State Art Gallery for the dissemination of visual production and Amazonian artists. Key words: visual arts; iconography; 1980’s; Amazonas; app